Comparison of Synthesis Strategies for a Dual-Polarized Reflectarray - Loic Marnat; Renaud Loison; Raphaël Gillard; Daniele Bresciani; Hervé Legay (International Journal of Antennas and Propagation)
This paper presents and compares four optimization strategies for printed reflectarrays. They are applied to synthesize a dual-polarized reflectarray using two kinds of slot-loaded patches. They provide objective criteria to deal with the numerous geometrical parameters available to tune the phase. The study relies on the comparative measurements of four different prototypes for the same 22𝜆0×22𝜆0 reflectarray (with 𝜆0 the wavelength at 𝑓0=14.25 GHz).